Everything I know about business : - Knox, Tim (J. Wiley & Sons, Inc., 2007)
Praise for Everything I Know About Business I Learned from My Mama "Not your typical success book by any means. It's laugh-out-loud funny, full of great stories and outstanding business ideas, and has real heart. This is one I would spend my money on!" -Larry Winget, New York Times bestselling author of It's Called Work for a Reason! and star of the A&E hit reality series Big Spender "Every now and then I find a book that is so inspiring I immediately start making a list of all the people I know who must have a copy. Everything I Know About Business I Learned from My Mama is one of those books." -Dan Miller, author of 48 Days to the Work You Love "This book is a great combination: both entertaining and educational. You'll get some terrific ideas and insights and have so much fun in the process, you might not even realize you're learning. I recommend it." -Mark Sanborn, author of The Fred Factor "This is one of those rare books that works on every level. Knox is an absolute pleasure to read, his stories are joyfully engaging, and there's a business lesson on every page. I enthusiastically recommend that you get this book immediately. Like me, you won't put it down until you've reached the last page. Hey, Tim, write another one soon!" -Joe Calloway, author of Work Like You're Showing Off! "Think of this book as Jeff Foxworthy meets Donald Trump. You get all of The Donald's wisdom dished up in some of the most hilarious business adventures ever described. Only Tim would learn a major business lesson from having his daddy try to electrocute him. If it ain't fun, don't do it. By that advice, you should read this book. It's an entrepreneur's gold mine nestled in a silly foam container." -Jerry Newman, author of My Secret Life on the McJob